Man and the environment : an introduction to human ecology and evolution - Boughey, Arthur S. (New York : Macmillan, 1971)
The term human ecology is not yet so well understood and established in contemporary idiom that it requires no explanation or definition.
1. Introduction -- 2. The Earliest Stages of Hominid Evolution -- 3. Pleistocene Hominids -- 4. Homo Erectus -- 5. The Origin of Urban Civilization -- 6. Human Diversity -- 7. Population Growth -- 8. Population Fluctuation -- 9. Population Control -- 10. Air Pollution -- 11. Water Pollution -- 12. Pesticides -- 13. Conservation -- 14. The Future.
Includes index.
Keywords: HUMAN ECOLOGY